From digital survey to serious game. A process of knowledge for the Ark of Mastino II - Sandro Parrinello; Alessia Miceli; Francesca Galasso (Disegnare con, 2021)
The Complex of the Scaliger Arks comprises several Gothic-style funerary monuments built by the Della Scala family, lords of Verona, to keep the memory of the illustrious dynasty. Among the tombs of the open-air funerary complex, located in the very historic core of the city, the arks of Cangrande I, Mastino II and Cansignorio stand out for their magnificence. Mastino II Della Scala, who ruled from 1329 to 1351, chose the current area as the family’s graveyard and its Ark is arguably the most important of the complex. It constitutes a singularity not only for its remarkable decorative apparatus, but also for its role of powerful communication tool in the urban context. Structural criticalities and material issues prompted the start of a knowledge process that aims at supporting restoration practices on the monument, but goes beyond that by proposing an innovative strategy for its valorisation based on a serious game. The research established a digital documentation protocol for the monument, achieving a high level of completeness without harming its precarious state of conservation. Then, from the results achieved, the activities pursued a virtuous process of dissemination in order to valorise one of the most important witnesses of the history of Verona. DOI: https://doi.org/10.20365/disegnarecon.27.2021.17